The Giving Of Disciplinary Penalty of Civil Servants Based On Government Regulation Number 53 of 2010 in Governments of Demak Regency - Muhammad Adib; Sri Kusriyah Kusriyah; Siti Rodhiyah Dwi Istinah (Jurnal Daulat Hukum, 2019)
Government Regulation No. 53 of 2010 regarding the discipline of the Civil Servant loading obligations, prohibitions, and disciplinary action which could be taken to the Civil Servant who has been convicted of the offense, is intended to foster a Civil Servant who has committed an offense, the form of disciplinary punishment is mild, moderate, and weight. Disciplinary punishment for the Civil Servant under Government Regulation No. 53 of 2010 Concerning the Discipline of Civil Servants. The formulation of this journal issue contains about how the process of disciplinary punishment, and constraints and efforts to overcome the impact of the Civil Servant disciplinary punishment in Government of Demak regency. The approach used in this study is a sociological juridical approach or juridical empirical, that is an approach that examines secondary data first and then proceed to conduct research in the field of primary data normative. The process of giving disciplinary sanctions for State Civil Apparatus in Government of Demak regency begins with the examination conducted by the immediate supervisor referred to in the legislation governing the authority of appointment, transfer and dismissal of civil servants. The results showed that in general the process of sanctioning / disciplinary punishment of civil servants in the Government of Demak be said to be good and there have been compliance with the existing regulations / applied in Government Regulation No. 53 of 2010, although it encountered the competent authorities judge still apply tolerance against the employee, but also a positive impact among their deterrent good not to repeat the same offense or one level higher than before either the Civil Servant concerned or the other. Obstacles in carrying out disciplinary punishment in Government of Demak regency environment is still low awareness of employees to do and be disciplined in performing the tasks for instance delays incoming work, lack of regulatory discipline, lack of supervision system and any violations of employee discipline. There must be constraints to overcome need for cooperation with other stakeholders comprising Inspectorate, BKPP, and the immediate superior civil servants in this way can be mutually reinforcing mutual communication, consultation, coordination so that if later there is a problem in the future could be accounted for.Keywords: Delivery of Disciplinary Sanctions; Civil Servant; Government Regulation No. 53 of 2010.